Revenue, New Products, and the Evolution of Music Quality since Napster - Luis Aguiar; Néstor Duch-Brown; Joel Waldfogel (European Commission, Joint Research Centre (JRC), 2015)
Recorded music revenue has fallen sharply since the appearance of the first digital sharing technology (Napster) in 1999. By 2012, it was down by about 70 percent in North America and Europe compared to 1999. Several factors may have contributed to this decline in revenue, including the change from physical CD formats to digital downloading and widespread file sharing. The fall in revenue raises a serious question about the viability of continued investment in new recorded music products, but it is not by itself the only question of interest for public policy. The purpose of copyright is precisely to protect investment in new artwork and give artists and producers a financial incentive to invest in new recordings. If that incentive is no longer strong enough to ensure a steady stream of new high-quality products, there may be a need for policy makers to intervene to reinforce copyright protection in music. From this perspective, the correct barometer for the health of the copyright system is whether creators bring forth valuable new products. The paper investigates the impact of recent technological change - that on may collectively term " - on the quantity and quality of music products produced in North America and 15 European countries. The number of new works has risen significantly since 2000; but the number of new products is a poor indicator of the value that society derives from music given the skew in sales distributions. Instead, one should take into account the evolution of the quality of new music products as well. The evolution of vintage quality can be inferred from consumption data by year and by vintage. In any given year, older music tends (on average) to sell less due to depreciation. Given data on sales by vintage for multiple calendar years, one can ask whether different vintages sell more or less than others, after accounting for depreciation. Using this approach on fragmentary sales data for the US only, Waldfogel (2012) found that the quality of music in the eyes of US consumers has grown sharply since Napster.
Keywords: 330; recorded music sales; digitization; internet; quality of music